Evaluation of outcomes of peritoneal dialysis patients in the post-covid-19 period: a national multicenter case-control study from Turkey - AŞICIOĞLU, EBRU (My University, 2022)
© 2022 S. Karger AG, Basel. Copyright: All rights reserved. No part of this publication may be translated into other languages, reproduced or utilized in any form or by any means, electronic or mechanical, including photocopying, recording, microcopying, or by any information storage and retrieval system, without permission in writing from the publisher.Introduction: There are not enough data on the post-CO-VID-19 period for peritoneal dialysis (PD) patients affected from COVID-19. We aimed to compare the clinical and laboratory data of PD patients after COVID-19 with a control PD group. Methods: This study, supported by the Turkish Society of Nephrology, is a national, multicenter retrospective case-control study involving adult PD patients with confirmed COVID-19, using data collected from April 21, 2021, to June 11, 2021. A control PD group was also formed from each PD unit, from patients with similar characteristics but without COVID-19. Patients in the active period of COVID-19 were not included. Data at the end of the first month and within the first 90 days, as well as other outcomes, including mortality, were investigated. Results: A total of 223 patients (COVID-19 group: 113, control group: 110) from 27 centers were included. The duration of PD in both groups was similar (median [IQR]: 3.0 [1.88-6.0] years and 3.0 [2.0-5.6]), but the patient age in the COVID-19 group was lower than that in the control group (50 [IQR: 40-57] years and 56 [IQR: 46-64] years, p < 0.001). PD characteristics and baseline laboratory data were similar in both groups, except serum albumin and hemoglobin levels on day 28, which were significantly lower in the COVID-19 group. In the COVID-19 group, respiratory symptoms, rehospitalization, lower respiratory tract infection, change in PD modality, UF failure, and hypervolemia were significantly higher on the 28th day. There was no significant difference in laboratory parameters at day 90. Only 1 (0.9%) patient in the COVID-19 group died within 90 days. There was no death in the control group. Respiratory symptoms, malnutrition, and hypervolemia were significantly higher at day 90 in the COVID-19 group. Conclusion: Mortality in the first 90 days after COVID-19 in PD patients with COVID-19 was not different from the control PD group. However, some patients continued to experience significant problems, especially respiratory system symptoms, malnutrition, and hypervolemia.
Keywords: Tıp; Dahili Tıp Bilimleri; İç Hastalıkları; Nefroloji; Yaşam Bilimleri; Sağlık Bilimleri; Temel Tıp Bilimleri; Biyokimya; Fizyoloji; Temel Bilimler; Medicine; Internal Medicine Sciences; Internal Diseases; Nephrology; Life Sciences; Health Sciences; Fundamental Medical Sciences; Biochemistry; Human Physiology; Natural Sciences; Klinik Tıp (MED); Yaşam Bilimleri (LIFE); Klinik Tıp; Biyoloji ve Biyokimya; ÜROLOJİ VE NEFROLOJİ; FİZYOLOJİ; Clinical Medicine (MED); Life Sciences (LIFE); CLINICAL MEDICINE; BIOLOGY & BIOCHEMISTRY; UROLOGY & NEPHROLOGY; PHYSIOLOGY; Üroloji; Fizyoloji (tıbbi); Physiology; Urology; Physiology (medical); Complication; COVID-19; Outcome; Peritoneal dialysis